Properties of some acousto-optical materials - KLESZCZEWSKI, Zygmunt (Archives of Acoustics, 1978)
The paper discusses the requirements to be met by the acousto-optical materials. Utilizing the scattering of laser light by acoustic wave, the measurements of the propagation velocity and absorption coefficients of acoustic waves and the photoelastic constants for Bi12Ge020, Bi12SiO28, TiO2 crystals and for SF-14 flint glass were made. On the basis of the above measurements acousto-optical parameters of the examined crystals have been calculated and subsequently discussed.